Sustainability Evaluation of Lake Batur Management in Bali Province: A Multidimensional Scaling Approach - Santi Arifani Kholida; Sri Mulatsih; Wonny Ahmad Ridwan (Postgraduate, University of Mataram, 2026)
Lake Batur has been designated as one of Indonesia's 15 priority lakes to be restored due to significant anthropogenic pressures from aquaculture, agriculture, tourism, and domestic waste. The purpose of this study is to evaluate the sustainability status of Lake Batur management through rapid appraisal techniques combined with a multidimensional scaling (MDS) approach using 18 attributes representing three dimensions, namely ecological, social, and economic dimensions. Data was collected from structured interviews with village leaders, field surveys, and secondary data from PODES 2024 and related agencies. Sustainability status varies significantly between villages and dimensions. In the ecological dimension, three villages showed a less sustainable status (32.75-45.53), while five villages achieved a fairly sustainable level (56.11-62.55). In the social dimension, four villages had a fairly sustainable status (51.04-64.87) and four villages had a less sustainable status (30.86-49.93). The results of the analysis on the economic dimension showed that five villages had a fairly sustainable status (51.39-65.68), two villages had a less sustainable status (33.33-39.90), and one village was not sustainable (22.60). Based on the leverage analysis, the flood frequency attribute is the most sensitive attribute in the ecological dimension, while in the social and economic dimensions, respectively, it lies in population density and the number of MSMEs.